Translation of the Genitive Absolute in the Armenian Alexander Romance: Exploring the Shift from Sensus de Sensu to Verbum de Verbo Approach - Kuntner, Rok (Matenadaran, 2024)
Abstract This article discusses the translation techniques employed in rendering the Greek genitive absolute in Book I of the Armenian Alexander Romance, amidst the transition from sensus de sensu to verbum de verbo translation approach. Through a comparative analysis of corresponding passages in the Armenian and Greek texts, six primary techniques are revealed — three leaning towards descriptive interpretations and three favouring a more literal rendition. These techniques align closely with those found in other translations labelled pre-Hellenising. The findings not only enhance our understanding of translation practices in the fifth and sixth century Armenia, but also provide valuable insights for the broader field of translation studies. Also, the results add evidence to the discussion of the still obscure question of continuity between the classical, pre-Hellenising, and Hellenising translations.
Keywords: pre-Hellenising translations.